THE IMPORTANCE OF MEDIA IN THE CONTEXT OF GLOBALIZATION (MEDICINE, PEDAGOGY AND TECHNOLOGY: THEORY AND PRACTICE, 2024)
This article highlights the importance of information and media in the context of globalization and its impact on national mentality. Threats of the media world are based on its place in the global world, the essence of the acceleration of globalization.